Dampak Fisiologis Kemoterapi Pada Anak Dengan Leukemia di Rumah Sakit - Herfiana, Sepsi; Arifah, Siti (Universitas Muhammadiyah Surakarta, 2019)
Leukemia is a most common children malignancy. Chemotherapy has been very effective in the management of leukemias. Chemotherapy is a systemic therapy, therefore the chemotherapy drug is not only directly related to the cancer but also damaged the normal tissue. Physiological effect of chemotherapy is important to be inspected because each individual is unique so it has different physiological effect, so it will require different treatment. The aim of this research is to understand physiological effect of chemotherapy in children with leukemia. This research is quantitative research, used descriptive analitic. The sample of this research were 30 sample with total sampling. The instrument used was a questionnaire of physiological effect of chemotherapy. The results showed that the physiological effect of chemotherapy were children with alopecia of 24 (80%) , Nausea of 17 (56.7%), vomiting of 16 children (53.3%); Decreased appetite of 14 children (46.7%); oral ulceration of 19 children (63.3%);Diarrhea of 3 children (10%); Fatigue of 14 children (46.7%); increase in risk factors for infection consisting of fever of 16 children (53.3%), cough of 13 children (43.3%), and flu of 8 children (26.7%); Bruises of 8 children (26.7%), bleeding of 14 children (46.7%); and other side effects there are 14 children (40%). The conclusion of this research is the most common physiological effects of children undergoing chemotherapy are alopecia, oral ulceration, nausea and vomiting, and fever